The moosicorn part III - Wurfel, Marlene (My University, 2022)
Lily is back for Season II of Tales from the Lilypad with an original story by Marlene Wurfel: The Moosicorn Part III. Mordecai is taking magic lessons from the Aurora Borealis. But what was his homework? Intro Music by Reid Alexander Whelton Sound Effects courtesy and Creative Commons Licence via freesound.org Lake sounds and warbler sounds by BenBonCan, Story Logo sound by SergeQuadrado
Keywords: storytelling; children's stories